The development of e-content ‘Sci-Anime2021’ for PDPR during Covid-19 era / Humaira Batrisyia Norzaimi ... [et al.] - Norzaimi, Humaira Batrisyia; Norzaimi, Iqlima Zulaiklia; Norzaimi, Qaisara Madilia; Abdul Rahman, Wahida (UiTM Cawangan Melaka Kampus Jasin, 2021)
E-Content is any form of learning material available digitally which a learner (students) access or interacts with teachers or among themselves to achieve related learning outcomes. E-Content is becomes popular because it allows flexibility in terms of time, place and pace of learning. However, in Malaysian education especially at primary school level, the development of E-Content is not widely developed due to the limitless of internet coverage, knowledge gap among teachers and awareness about E-Content. Therefore, the development of Sci-Anime2021 was introduced in order to help students specifically Tahap 2 Kurikulum Standard Sekolah Rendah (KSSR) students to increase their understanding towards certain topics in Science subject. Sci-Anime2021 separated to three major components, which are the development process of Sci-Anime2021, final product E-Content Sci-Anime2021 and assessment in Sci- Anime2021. This E-Content developed by using combination of smart phone applications (FlipaClip & CapCut). Animations in Sci-Anime2021 were created by using FlipaClip whereas video editing process was conducted using CapCut. Finally, the assessment was prepared using EdPuzzle. Then, the link of assessment will be posted in Google Classroom. Google Classroom will be a platform to discuss and interact with teacher and other students regarding the assessment and E-Content. Therefore, the development of Sci-Anime2021 will be able to help students during current Pengajaran dan Pembelajaran di Rumah (PdPR) in Covid-19 era. The learning process will be more fun and interactive through animation, which includes text, video, images and sounds.